التكاليف الاقتصادية للاحتلال الإسرائيلي على الشعب الفلسطيني: تكاليف مالية تراكمية - United Nations Conference on Trade; Development (United Nations, 2020)
The study addresses the leakage of Palestinian fiscal revenue to Israel and provide up-to-date data on the sources of losses of Palestinian fiscal resources. It explains that the fiscal costs are part of the overall economic costs caused by occupation and consists of two components: (i) Palestinian fiscal leakage to Israel under the PER, and (ii) other fiscal losses that are not leaked to Israel but caused by policies and measures imposed under the prolonged occupation.